(untitled) (International Conference on Scientific Research in Natural and Social Sciences, 2025)
The development of educational vocabulary plays a crucial role in teaching the mother tongue effectively. This paper explores various strategies for integrating and expanding the vocabulary used in mother tongue education. By focusing on the incorporation of both traditional and modern techniques, such as context-based learning, active participation, and digital tools, the study highlights how vocabulary can be developed in a way that enhances students’ language comprehension and communication skills. Emphasizing a comprehensive approach that includes both theoretical frameworks and practical applications, the paper aims to provide educators with strategies for fostering linguistic proficiency in their students, ensuring a deeper connection with their cultural and linguistic heritage. Additionally, it looks into the importance of vocabulary acquisition in early education and its long-term benefits in both academic and social contexts.